Normes de genre et subversions : le rôle des influenceuses dans le body positivisme et le féminisme numérique - Florian Dauphin (Communication)
This paper explores the role of female social media influencers in reproducing and subverting gender norms and stereotypes. Using a qualitative methodology comprising semi-structured interviews and content analysis, we examined a broad sample of female influencers active on Instagram, YouTube, and TikTok. The results reveal a dual dynamic: on the one hand, female influencers often play a role in standardizing gender norms in their quest for visibility and recognition; on the other, some use their influence to challenge and deconstruct these same norms through movements such as body positivity. These practices are influenced by sociotechnical, economic, and cultural constraints and show that social media makes it possible to both reproduce and challenge hegemonic norms.